RANCANG BANGUN SISTEM INFORMASI POS PELAYANAN TERPADU PADA DINKES SURABAYA BERBASIS WEB - Wahyuni, Anita Dwi; Sunarto, MJ.Dewiyani; Amelia, Tan (Jurnal Sistem Informasi dan Komputerisasi Akuntansi (JSIKA), 2015)
POSYANDU was built to pay attention to the health of mothers and children in some areas of the village. POSYANDU every month give the inspection report to the PUSKESMAS to be reported to the Health Office of Surabaya. Due to the large number of POSYANDU and limitations of midwives then the midwife to handle many Posyandu each month.Making the POSYANDU examination report that has been happening is still done manually because it has no information system. Because one midwife to handle some of the POSYANDU and the midwife often experienced delays in preparing reports and often put off. Due to delays in reporting, it can inhibit the Head of Puskesmas in monitoring maternal and child health in the region supervised POSYANDU and this also resulted in delays in the distribution of health centers report to the health office. The slower the reporting received then the slower Puskesmas monitoring and evaluation of the health of infants and pregnant women. Based on this problem, then the solution is made is to design and build a web-based integrated health information systems that can facilitate report generation and distribution of reports and facilitate the health office in monitoring the results of POSYANDU report.Results from the trial showed that this information system can provide convenience in the process of manufacture and distribution of reports and monitoring the health of children and pregnant women in the area of Surabaya.